Characterization and valorization of biogas digestate and derived organic fertilizer products from separation processes - Romio, Cristiane; Ward, Alastair James; Møller, Henrik Bjarne (Frontiers in Sustainable Food Systems, 2024)
Introduction Anaerobic digestion of manure, together with other biowastes, produces biogas that can substitute fossil energy and thereby reduce CO2 emissions and post- digestion greenhouse gas emissions. The final digestate of the process is an organic fertilizer rich in plant nutrients and recalcitrant organic constituents. The digestate characteristics and quality depend on several parameters, such as input feedstocks and operational conditions of the biogas plants. In Denmark, the rapid expansion of the biogas sector in recent years has resulted in a great variety of feedstocks used in the plants. The first generation of biogas plants mainly treated manure, industrial wastes, and energy crops with short retention times, while the new generation of biogas plants are co-digesting manure with higher amounts of lignocellulosic feedstocks and operating with longer retention times. This study evaluated whether this shift in feedstock composition could impact the fertilizer quality and post-digestion greenhouse gases and ammonia emissions during storage and application of digestate. Methods Digestate samples from 2015 to 2023 were collected and analyzed for composition and residual methane yields. The efficiencies of solid–liquid separation applied to several digestate samples from the new generation of biogas plants were investigated and the nutrients contents of the liquid and solid fractions of digestate were evaluated. Results and discussion The most evident change caused by the feedstock transition was an average increase of 52% in the total solids content of digestate, which can negatively impact ammonia emissions during digestate application. In contrast, similar average residual methane yields on a fresh matter basis of approximately 5 L/kg indicated comparable risks of methane emissions during storage. The liquid fraction of industrially separated digestate presented, on average, nutrient concentrations similar to those of unseparated digestate, while the solid fraction presented similar K, lower total ammoniacal nitrogen, and higher organic N and P contents than unseparated digestate on a fresh matter basis. The average residual methane yield of the industrially separated solid fraction of digestate was 101 L/kg volatile solids, while the average calorific value was 21 MJ/kg volatile solids, indicating its potential for additional energy generation.